Pattern reconfigurable dielectric resonator antenna using capacitor loading for internet of things applications - Aymen Dheyaa Khaleel; Osman Ghazali; Aqeel Mahmood Jawad; Ayman Mohammed Ibrahim; Massudi Mahmuddin; Ahmed Jamal Abdullah Al-Gburi; Mohammed Najah Mahdi (Institute of Advanced Engineering and Science, 2023)
This research study presents a cube dielectric resonator antenna (DRA) with four different radiation patterns for internet of things (IoT) applications. The various radiation patterns are determined by the grounded capacitor loading to reduce interference. The DRA is constructed of ceramic material with a dielectric constant of 30 and is fed via a coaxial probe located in the antenna’s center. Capacitors are used to load the four parasitic microstrip feed lines. Each pattern of radiation is adjustable by adjusting the capacitors loading on the feed line. The proposed antenna works at 3.5 GHz with -10 narrow impedance bandwidth of 74 MHz.